2017
DOI: 10.1099/mic.0.000438
|View full text |Cite
|
Sign up to set email alerts
|

A chitinase is required for Xylella fastidiosa colonization of its insect and plant hosts

Abstract: Xylella fastidiosa colonizes the xylem network of host plant species as well as the foregut of its required insect vectors to ensure efficient propagation. Disease management strategies remain inefficient due to a limited comprehension of the mechanisms governing both insect and plant colonization. It was previously shown that X. fastidiosa has a functional chitinase (ChiA), and that chitin likely serves as a carbon source for this bacterium. We expand on that research, showing that a chiA mutant strain is una… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 39 publications
(74 reference statements)
0
12
0
1
Order By: Relevance
“…Chitinases are widely distributed in prokaryotic and eukaryotic cells, and have diverse biological functions (Langner and Göhre, 2016); for example, the bacterial pathogen Xylella fastidiosa secretes chitinase that hydrolyzes the chitin of its host fungi and insects for use as a carbon source (Labroussaa et al, 2017). Fungal pathogens use chitinases to continuously remodel their cell wall plasticity during growth and infection (Langner and Göhre, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Chitinases are widely distributed in prokaryotic and eukaryotic cells, and have diverse biological functions (Langner and Göhre, 2016); for example, the bacterial pathogen Xylella fastidiosa secretes chitinase that hydrolyzes the chitin of its host fungi and insects for use as a carbon source (Labroussaa et al, 2017). Fungal pathogens use chitinases to continuously remodel their cell wall plasticity during growth and infection (Langner and Göhre, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…X. fastidiosa is specifically restricted to two environments (plant vascular vessels and the foregut of xylem-eating insects) (15). These environments have common features as they are both constituted of xylem sap and carbonated polymers (plant cell wall and chitin), and it has been shown that the chitin-degrading enzyme is essential for colonization both in the insect and in planta (45). Thereby, X. fastidiosa appears to be restricted to a homeostatic environment, i.e., overall constant in composition and not prone to external perturbations.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, X. fastidiosa spread has been mathematically and experimentally demonstrated to peak prior to full disease symptom development, a point at which within-plant bacterial populations are large and acquisition by vectors is maximized, but insects strongly discriminate against such plants (39). Finally, although X. fastidiosa may negatively impact plants in different ways, the only evidence of potential negative effects on insect vectors is recent work demonstrating that the population size of a chitinase mutant strain did not increase in insect vectors when compared with a wild-type control (81), suggesting that vector colonization by X. fastidiosa involves chitin degradation. Although this could impact insect hosts, there is no direct evidence that X. fastidiosa colonization leads to vector behavioral or fitness-related changes.…”
Section: Emergence Of Xylella Fastidiosa In Europementioning
confidence: 99%
“…First, as mentioned above, there is no evidence of X. fastidiosa genotype-vector specificity, indicating that biological and molecular interactions between the pathogen and vector are phylogenetically conserved. Once acquired from plants, X. fastidiosa attaches to and colonizes specific regions in the foregut of vectors (i.e., precibarium and cibarium) to form a persistent biofilm (76,81,118). The fact that X. fastidiosa is propagative and persistent yet noncirculative in insect vectors has been demonstrated with several lines of evidence, including the lack of transovarial (58) and transstadial (5,117) transmission of bacterium in vectors, microscopical observations of the foregut (6,17,118), transmission studies with aging insects (6,69), and other approaches demonstrating bacterial persistence and multiplication in vectors (69,76,81).…”
Section: Vector Transmissionmentioning
confidence: 99%